Drowned: Anishinabek Economies and Resistance to Hydroelectric Development -in the Winnipeg River Drainage Basin, 1873-1975 - Luby, Brittany Alexandra (York University, 2020)
In 1893 the Keewatin Lumber and Power Company planned the first hydroelectric generating station on the north shore of Lake of the Woods (near present-day Kenora, Ontario). Approximately fifty years later, federal officials seeking employment for Canadian veterans turned to Northwestern Ontario and its underutilized water resources, envisioning a manufacturing hub on the Precambrian Shield. Between 1950 and 1958, the Hydroelectric Power Commission of Ontario remodeled the Winnipeg River drainage basin to produce power for federally-sanctioned peacetime industries, namely pulp and paper production. To redesign the Winnipeg River drainage basin, however, hydro officials needed to encroach on Anishinabek lands: both federally-recognized reserves and unrecognized, but heavily occupied, ancestral territories. This dissertation tells the story of how Anishinabek families used a diverse array of strategies adaptation, cooperation, and passive resistance to manage environmental change caused by Whitedog Falls Generating Station. Anishinabek families worked to stabilize their communities in an era of imposed environmental and economic change. Historians have long argued that hydroelectric development is necessarily at odds with Indigenous culture and subsistence economies. This dissertation provides a counter-narrative, arguing that cultural and economic damage, although linked to environmental damage, correlated more strongly with Anishinabek exclusion from resource negotiations. Moreover, this work complicates historical representations of a uniform Indigenous response to development. Given limited negotiations between the Hydro-Electric Power Commission and local First Nations, Anishinabek families did not respond to industrial incursions with one representative voice. The process of development itself, I argue, prevented a unified community response. As a result, Anishinabek communities fractured in response to hydroelectric development.